Wood dust effects on carpenters pulmonary function test parameters: a comparative study - Noura Mohamed Elfatih; Ibrahim Abdelrhim Ali; Muaath Ahmed Mohammed; Izzut Awad Ahmed; Nouralsalhin Abdalhamid Alaagib; Omer Abdelaziz Musa (BMC Pulmonary Medicine)
Abstract Background Few studies have investigated the effects of wood dust on carpenters, who are frequently exposed to this hazardous material. This study aimed to determine the effects of wood dust exposure on carpenters pulmonary function test (PFT) parameters. Methods This comparative cross-sectional community-based study included 130 participants; a group of carpenters and a matched cohort. Standard techniques were used to measure each participant’s force vital capacity (FVC), force expiratory volume in one second (FEV1), FEV1/FVC ratio, and peak expiratory flow rate (PEFR). Statistical tests were employed to investigate different variables. A P value of < 0.05 is considered significant. Results Carpenters had a mean age of 51.6 ± 19.9 years, whereas the matched cohort had a mean age of 49.8 ± 13.9 years. Approximately 23 (35.4%) carpenters experienced respiratory problems. Carpenters had significantly lower FEV1, FVC, FEV1/FVC%, and PEFR values than the matched cohort (P < 0.001). Additionally, the association between the carpenters duration of exposure to wood dust and their PFT values showed a significant statistical difference (P < 0.05). Likewise, the correlation between the duration of exposure to wood dust and their PFT values was significant (< 0.001). Conclusions Wood Dust’s Effects on carpenters’ respiratory systems are worth further discussion. Awareness campaigns should be undertaken to educate carpenters about lung health and preventative measures.